Comparing the usability of the World Health Organization's conventional tuberculosis guidelines to the eTB recommendations map: A two-arm superiority randomised controlled trial - Micayla Matthews; Tamara Lotfi; Nancy Santesso; Mark Loeb; Dominik Mertz; Zain Chagla; Anisa Hajizadeh; Thomas Piggott; Bart Dietl; Holger J. Schünemann (Public Library of Science (PLoS), 2022)
Best practices for the dissemination of global health guidelines has not undergone rigorous research. We used a new approach to digitizing World Health Organization (WHO) global tuberculosis guideline recommendations (eTB RecMap) and compared its usability to the conventional method of accessing TB recommendations using the WHO website. We conducted a two-arm superiority randomised controlled trial using a survey among global stakeholders who were past or planned future users of TB guidelines, recommendations, or policy advice. We assigned participants randomly (1:1) to complete an activity using the WHO eTB RecMap or the conventional website. The primary outcome was the accessibility of information and secondary outcomes understanding, satisfaction, and preference for one of the two formats. Between February 26 and August 29, 2021, we received 478 responses from stakeholders, of whom 244 (122 per group) were eligible and provided analysable results. Participants rated the eTB RecMap as more accessible, on average, when compared to the conventional website (on a seven-point scale, the mean difference MD was 0.9; 95% confidence interval CI: 0.6, 1.2; p < 0.001) and were more likely to correctly answer understanding questions. This is the first trial comparing digitized dissemination formats of health guideline recommendations. Stakeholders rated the WHO eTB RecMap as more accessible than the conventional WHO website for the tested recommendations. They also understood presented information better. The findings support better usability of TB information through the eTB RecMap and contribute to the effort to end the TB epidemic. Trial registration: This trial was registered with ClinicalTrials.gov (NCT04745897) on February 9, 2021.